The Association of RAS Association Domain Family Protein1A (RASSF1A) Methylation States and Bladder Cancer Risk: A Systematic Review and Meta-Analysis - Gao, Tianyi; Wang, Shukui; He, Bangshun; Pan, Yuqin; Song, Guoqi; Gu, Ling; Chen, Liping; Nie, Zhenling; Xu, Yeqiong; Li, Rui (PLOS ONE, 2012)
RAS association domain family protein 1a (RASSF1A) is a putative tumor suppressor gene located on 3p21, has been regarded playing important roles in the regulation of different types of human tumors. Previous reports demonstrated that the frequency of RASSF1A methylation was significantly higher in patients group compared with controls, but the relationship between RASSF1A promoter methylation and pathological features or the tumor grade of bladder cancer remains controversial. Therefore, A meta-analysis of published studies investigating the effects of RASSF1A methylation status in bladder cancer occurrence and association with both pTNM (p, pathologic stage; T, tumor size; N, node status; M, metastatic status) and tumor grade in bladder cancer was performed in the study. A total of 10 eligible studies involving 543 cases and 217 controls were included in the pooled analyses. Under the fixed-effects model, the OR of RASSF1A methylation in bladder cancer patients, compared to non-cancer controls, was 8. 40 with 95%CI = 4. 96–14. 23. The pooled OR with the random-effects model of pTNM and tumor grade in RASSF1A methylated patients, compared to unmethylated patients, was 0. 75 (95%CI = 0. 28–1. 99) and 0. 39 (95%CI = 0. 14–1. 09). This study showed that RASSF1A methylation appears to be an independent prognostic factor for bladder cancer. The present findings also require confirmation through adequately designed prospective studies.